ответ:
1) 2(3x + 1) - x ≤ 3(x + 4), 2) 7x + 4(x - 2) > 6(1 + 3x),
6х + 2 - х ≤ 3х + 12, 7х + 4х - 8 > 6 + 18x,
5х + 2 ≤ 3х + 12, 11x - 8 > 6 + 18x,
5х - 3х ≤ 12 - 2, 11x - 18x > 6 + 8,
2х ≤ 10, -7x > 14,
х ≤ 5,
х ∈ (-∞; 5];
подробнее - на -
пошаговое объяснение:
ответ:
1) 2(3x + 1) - x ≤ 3(x + 4), 2) 7x + 4(x - 2) > 6(1 + 3x),
6х + 2 - х ≤ 3х + 12,
7х + 4х - 8 > 6 + 18x,
5х + 2 ≤ 3х + 12, 11x - 8 > 6 + 18x,
5х - 3х ≤ 12 - 2,
11x - 18x > 6 + 8,
2х ≤ 10,
-7x > 14,
х ≤ 5,
х
∈ (-∞; 5];
подробнее - на -
пошаговое объяснение: